2017
DOI: 10.1016/j.jesp.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Reversing implicit first impressions through reinterpretation after a two-day delay

Abstract: People are adept at forming impressions of others, but how easily can impressions be updated? Although implicit first impressions have been characterized as difficult to overturn, recent work shows that they can be reversed through reinterpretation of earlier learning. However, such reversal has been demonstrated only in the same experimental session in which the impression formed, suggesting that implicit updating might be possible only within a brief temporal window, before impressions are consolidated and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 44 publications
7
46
0
Order By: Relevance
“…Second, the current findings are silent about whether the observed changes in deep-rooted implicit evaluations persist over time or generalize across contexts. It is possible that negative information becomes highly accessible immediately after acquisition, when its impact on implicit evaluation peeks (but see Mann & Ferguson, 2017, for evidence that changes in newly learned implicit evaluations do persist over time). It is also possible that the observed changes in implicit evaluations are context-dependent (e.g., limited to the context in which they were learned, see Gawronski, Rydell, De Houwer, Brannon, Ye, Vervliet, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the current findings are silent about whether the observed changes in deep-rooted implicit evaluations persist over time or generalize across contexts. It is possible that negative information becomes highly accessible immediately after acquisition, when its impact on implicit evaluation peeks (but see Mann & Ferguson, 2017, for evidence that changes in newly learned implicit evaluations do persist over time). It is also possible that the observed changes in implicit evaluations are context-dependent (e.g., limited to the context in which they were learned, see Gawronski, Rydell, De Houwer, Brannon, Ye, Vervliet, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…That means that without active efforts to sustain short-term shifts created in the lab, these shifts are likely to be wiped away upon re-exposure to the social environment (Forscher et al, 2017;cf. De Houwer, 2009;Mann & Ferguson, 2017). In fact, one recent series of studies found that nine interventions that reduced response biases on implicit tasks immediately showed little to no lasting impact days later (Lai et al, 2016).…”
Section: Generalizability Of Implicit Measure Changementioning
confidence: 99%
“…Since its creation, the AMP has attracted considerable attention and use in psychological science. It is most commonly used in social psychology to assess automatic evaluations in racial (Payne et al, 2005;Ditonto, Lau, & Sears, 2013; although see Teige-Mocigemba, Becker, Sherman, Reichardt, & Klauer, 2017), gender (Ye & Gawronski, 2018), sexuality (Imhoff, Schmidt, Bernhardt, Dierksmeier, & Banse, 2011), and political domains (Payne et al, 2005;Kalmoe & Piston, 2013), to investigate the potential origins of attitudes and stereotypes (Dunham & Emory, 2014;Mann et al, 2019;Van Dessel, Mertens, Smith, & De Houwer, 2017), and to assess the effectiveness of interventions designed to change automatic evaluations within those domains (Mann & Ferguson, 2017). In clinical psychology, the AMP is often used to assess, or even provide prospective prediction of, psychopathological behaviors such as eating disorders, non-suicidal self-injury, alcoholism, anxiety, depressive symptoms, and physical abuse of children (Fox et al, 2018;Görgen, Joormann, Hiller, & Witthöft, 2015;Jasper & Witthöft, 2013;McCarthy, Skowronski, Crouch, & Milner, 2017;Smith, Forrest, Velkoff, Ribeiro, & Franklin, 2018;Zerhouni, Bègue, Comiran, & Wiers, 2018).…”
Section: Use Of the Amp Is Widespread And Variedmentioning
confidence: 99%